APPLICATION DEVELOPMENT OF EARTHQUAKES DISASTER PREPAREDNESS FOR CHILDREN - Gustalika, Muhamad Azrino; Usman, Muhammad Lulu Latif; Bahtiar, Arief Rais (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
Indonesia is a country in the ring of fire and one of the most disaster-prone countries on the planet. As a result of these characteristics, Indonesia is vulnerable to earthquakes at any time. For the children, the earthquake was a traumatic experience. They were overcome with panic and dread. The victims of earthquakes and tsunamis are also susceptible to nightmares related to the natural disasters they have witnessed. As a result, there is a need for early childhood learning development media to deal with earthquakes, one of which is an android application. This program is designed for early childhood earthquakes and childrenâ€™s attempts to comprehend earthquakes. For media development, this study uses the System Development Life Cycle method with Waterfall methodology and BlackBox testing. The results of the application test using BlackBox when generating all scenarios were successfully executed according to the expected results using three different device brands, including Xiaomi, Asus, and Samsung.Â